Provincial Factor Inputs and Economic Growth in China: A Panel Autoregressive Distributed Lag Model Method - Fu, Yanyan; Gan, Pei-Tha; Gamal, Awadh Ahmed Mohammed; Ramli, Norimah (International Journal of Economics and Financial Issues, 2025)
A notable feature of empirical research into the forces of China's economic growth in an innovation-driven economy is the limited focus on whether the traditional reliance on factor inputs has been undermined by technical change. To address this shortfall, this study uses the endogenous growth model to measure the roles of factor inputs. It examines empirical validity based on a sample of China’s top six economic powerhouses, namely, Guangdong, Jiangsu, Shandong, Zhejiang, Henan, and Sichuan Province. Using panel autoregressive distributed lag method, the findings suggest that policymakers should not ignore the explanatory power of factor inputs, namely, physical capital, labor, human capital, and research and development on economic growth in navigating economic evolution by relying on increasing quantities of inputs to focus on improving the efficiency and quality of those inputs. Through their accumulation and utilization in production processes, these factor inputs may collectively enhance an economy’s production capabilities and growth potential.